Self-assembly behavior of hairy colloidal particles with different architectures mixed versus janus - Kirillova, A (Langmuir : the ACS journal of surfaces and colloids, 2014)
In this paper, we investigated the aggregation and assembly behavior of hairy core-shell particles with different architectures consisting of a hard silica core and soft polymer brush shells. We varied the nature of the polymers which form the shell: we used different hydrophilic positively (poly(2-(dimethylamino)ethyl methacrylate), PDMAEMA) and negatively (poly(acrylic acid), PAA) charged polymers, uncharged hydrophilic (polyethylene glycol, PEG) polymers, and hydrophobic (poly(lauryl methacrylate), PLMA; polystyrene, PS) polymers. We synthesized particles covered by polymer of one sort (homogeneously coated particles) as well as Janus particles (two polymers are grafted to the opposite sides of the core) and investigated/compared the aggregation behavior of different fully covered particles, their mixtures, and Janus particles